Social media and communication media. case study: “el informador” newspaper (Barquisimeto, Venezuela) (Dissertare, 2018)
Among the most recent technological novelties in the area of ​​computing, we can come across social networks. This type of web services came to light as an option to interact and socialize. In Venezuela, its high dissemination has persuaded the traditional media to expand its influence through them. The given situation encourages the development of the present study, whose purpose is to describe how the social networks such as Facebook and Twitter are managed in “El Informador” newspaper (Barquisimeto, Lara state, Venezuela). For this, the public presence, function and activity dimensions are used. Additionally, some comparisons with the social networks of two printed media of Lara state are presented. The research is descriptive, with a non-experimental transectional field design, carried out in the period November 2014-June 2015. The technique of direct observation was used to obtain data such as: messages, types of message, and types of interactions established by the readers, among others. They were analyzed using descriptive statistics and calculation of indicators proposed in previous studies on the subject. The results show that the main use established by the newspaper El Informador on Facebook and Twitter is to spread information. Additionally, the vocation of the social networks analyzed is mainly journalistic. In conclusion, the use of these networks is framed in a strategic vision of optimal use of ICT, as a mechanism to ensure the sustainability of the organization, strengthening the presence of its brand in the market-goal, in order to ensure the fidelity of the readers.
Keywords: social networks; media; management